Migrating two legacy systems to SOA: a new approach for service selection based on data flow diagram. (4th July 2019) - Bani-Ismail, Basel; Baghdadi, Youcef
There are many service identification methods (SIMs) to simplify service identification in SOA lifecycle. These SIMs vary in terms of their features (e.g., input artefact, technique). Due to this diversity, few evaluation frameworks have been proposed to guide organisations in selecting a suitable SIM based on their available input artefacts (e.g., source code, business process). This research concerns with SIMs that consider data flow diagram (DFD) as an input artefact, in order to migrate two legacy systems, modelled with DFD, to SOA. Only two SIMs are found in the literature to identify services based on DFD. However, these SIMs do not provide a way to select among the services identified to be implemented as web services. Therefore, this paper aims to bridge this gap by proposing a new approach for service selection based on DFD to assist organisations in speeding up the process of migrating their legacy systems to SOA.